Effects of Two Different Femoral Referencing Systems in Total Knee Arthroplasty on Immediate to Early Clinical Outcomes - Boonyanuwat, MD, Wittawat; Tanavalee, MD, Aree; Tanasubsinn, MD, Natee; Ngarmukos, MD, Srihatach (Journal of Southeast Asian Orthopaedics, 2022)
Purpose: Basically, there are two different femoral referencing systems in total knee arthroplasty (TKA): anterior referencing system (ARS) and posterior referencing system (PRS). Selected femoral component based on ARS or PRS for individual patient, especially in-between size, which provide good knee kinematics and well soft tissue balance is among one of the surgical goals. However, there are few reports on advantages, disadvantages and clinical outcomes of TKA using both femoral referencing systems. We prospectively evaluated the effect of both femoral referencing systems in TKA on immediate to early clinical outcomes. Methods: Eighty-one patients who had uncomplicated primary unilateral TKA were randomly divided into 2 groups; the ARS group and the PRS group, respectively. All patients underwent similar surgical techniques and postoperative protocol, except the step of femoral sizing according to the ARS group and the PRS group. Knees with measured in-between size of the femoral component were chosen a smaller size in the ARS group and a larger size in the PRS group. Patients were evaluated and compared to range of motion (ROM), visual analog scale (VAS), quadriceps peak torque (QPT), the Knee Society System (KSS) score and Short Form- 36 (SF-36) score, preoperatively, and at 2-week, at 6-week, at 3-month and at 6-month follow-up (FU). Results: There were 61 females and 20 male patients with the average age and BMI of 70.6 years and 27.8 Kg/m2, respectively. Forty-o e patients and 40 patients were in the ARS group and the PRS group respectively. Sixteen patients in the ARS group and 17 patients in the PRS group had in-between size of the femoral component. All patients had gradually improved knee ROM, VAS, QPT, KSS score, and SF-36 at all FU visits with significant differences at 6-month compared to preoperative evaluation. There were no statistical differences in all investigated parameters between the ARS group and the PRS group. Similar, at 6-month FU, there were no differences in all investigated parameters of the in-between size subgroup of ARS and PRS. There were no complications related to using both femoral referencing TKA systems. Conclusion: Both ARS and PRS for TKA demonstrated no differences in ROM of the knee, VAS, QPT, KSS score, and SF-36 during follow-up to six months. The concept to select a smaller femoral size for ARS and a larger size for PRS did not provide clinical differences, especially in ROM and QPT at early FU. We concluded that both contemporary TKA knee systems provided similar early clinical outcomes, regardless of matched or in-between femoral size.